Anthropometric measures of young Nigerians for ergonomic furniture design - Fidelis OP; Ogunlade B; Adelakun SA (Journal of Biology and Medicine - Peertechz Publications, 2019)
Background: Ergonomic furniture design which is based on the application of the anthropometric measurements of the intended users does not only reduce the risk of developing musculoskeletal disorders such as low back pain, but also improves work performance. Aim: The main aim of this study was to survey and describe Nigerian University students based on important anthropometric measures relevant to ergonomic classroom furniture design.